2020
DOI: 10.1002/vms3.375
|View full text |Cite
|
Sign up to set email alerts
|

Gamithromycin in swine: Pharmacokinetics and clinical evaluation against swine respiratory disease

Abstract: The pharmacokinetics of gamithromycin were evaluated in 26 male castrated and female crossbred swine administered gamithromycin 15% w/v (Zactran®, Boehringer Ingelheim) intravenously at 6 mg/kg bodyweight or intramuscularly at 3, 6 or 12 mg/kg bodyweight. Blood samples were collected up to Day 10 to establish the plasma profile of gamithromycin, bioavailability and dose proportionality. When administered by intramuscular injection at 6 mg/kg BWT, pharmacokinetic parameters were as follows: area under the curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…This data was used to establish a reliable in vivo and in vitro correlation. In addition, similar PK profiles in sheep, cattle, and swine further support the fact that GAM has similar absorption, distribution, metabolism, and elimination properties across the species [65][66][67]. Considering the available data for this minor species (sheep), a non-radiolabeled marker residue study for determination of the M/T ratios in edible tissues and a combination of cold semi-quantitative LC-HRMS and quantitative triple quadrupole LC-MS/MS approach was carried out [61] and accepted by the European Medicines Agency (EMA) [64] to have adequately defined the human food safety profile of Zactran in sheep.…”
Section: Feasibility Of Conducting Non-radiolabeled Study To Evaluate...mentioning
confidence: 61%
“…This data was used to establish a reliable in vivo and in vitro correlation. In addition, similar PK profiles in sheep, cattle, and swine further support the fact that GAM has similar absorption, distribution, metabolism, and elimination properties across the species [65][66][67]. Considering the available data for this minor species (sheep), a non-radiolabeled marker residue study for determination of the M/T ratios in edible tissues and a combination of cold semi-quantitative LC-HRMS and quantitative triple quadrupole LC-MS/MS approach was carried out [61] and accepted by the European Medicines Agency (EMA) [64] to have adequately defined the human food safety profile of Zactran in sheep.…”
Section: Feasibility Of Conducting Non-radiolabeled Study To Evaluate...mentioning
confidence: 61%
“…gamithromycin injection (Zactran®), developed by the French company Merial, was approved by the European Union to treat BRD caused by M. haemolytica, P. multocida, and H. somni. Gamithromycin has the advantages of a broad antibacterial spectrum, rapid absorption, lasting e cacy, safety, and low toxicity and has overall application prospects in livestock and poultry breeding production [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Gamithromycin is a semisynthetic azalide that is approved for the treatment of SRD due to A. pleuropneumoniae and Pasteurella multocida ( 6 , 7 ). Intramuscular and subcutaneous administrations have been developed with promising pharmacokinetic and efficacy results in pigs ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intramuscular and subcutaneous administrations have been developed with promising pharmacokinetic and efficacy results in pigs (8,9). Our previous pharmacokinetic/pharmacodynamic (PK/PD) studies in piglets have demonstrated the potency and efficacy of gamithromycin for Haemophilus parasuis (6). Given that gamithromycin has activity against a wider range of respiratory pathogens and other macrolides/azalides are used for the treatment of respiratory tract infections (6,(10)(11)(12), a logical consideration is to what extent gamithromycin could be valuable for S. suis infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation